Chosen Name Use Is Linked to Reduced Depressive Symptoms, Suicidal Ideation, and Suicidal Behavior Among Transgender Youth - Russell, Stephen T.; Pollitt, Amanda M.; Li, Gu; Grossman, Arnold H. (Journal of adolescent health, 2018)
This study aimed to examine the relation between chosen name use, as a proxy for youths' gender affirmation in various contexts, and mental health among transgender youth. Data come from a community cohort sample of 129 transgender and gender nonconforming youth from three U.S. cities. We assessed chosen name use across multiple contexts and examined its association with depression, suicidal ideation, and suicidal behavior. After adjusting for personal characteristics and social support, chosen name use in more contexts was associated with lower depression, suicidal ideation, and suicidal behavior. Depression, suicidal ideation, and suicidal behavior were lowest when chosen names could be used in all four contexts. For transgender youth who choose a name different from the one given at birth, use of their chosen name in multiple contexts affirms their gender identity and reduces mental health risks known to be high in this group.